Bullying among School Students: Family Group Conference as an Alternative to Punishment: (Buli dalam Kalangan Pelajar Sekolah: Persidangan Kumpulan Keluarga sebagai Alternatif kepada Hukuman) (Kanun: Jurnal Undang-undang Malaysia, 2020)
Bullying among school students cannot be taken lightly. There are specific guidelines and policies in Malaysia that allow school authorities to take disciplinary action against bullying. Legal action can also be taken against the perpetrator if necessary. However, Family Group Conference have been adopted in some countries as alternatives to punishment for bullying in schools. This study is conducted in order to examine bullying among school students in Malaysian schools, as well as the laws governing school bullying. This research also analyses the resolution of school bullying through Family Group Conferences as alternatives to punishment as practised in several countries. It is recommended that Family Group Conferences be introduced in Malaysia to complement the current solutions for school bullying cases. This study utilizes a qualitative method, referring to Acts, decided cases, and academic writings such as books and journals.Keywords: School bullying, child offenders, Family Group Conference